2013
DOI: 10.1016/j.jacc.2013.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Patient Outcome Following 2 Different Stress Imaging Approaches

Abstract: Perfusion imaging with RTMCE improves the detection of CAD during stress echocardiography, and identifies those more likely to undergo revascularization following an abnormal study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 22 publications
0
40
0
3
Order By: Relevance
“…12 Patients with abnormal MP with and without WM abnormalities were significantly more likely to undergo LR (6.3% [seven of 111] patients with normal MP vs 18.6% [16 of 86] patients with abnormal MP), a finding also noted in the recent Prospective Evaluation of Outcomes with Stress Perfusion Imaging versus Stress Wall Motion Imaging during Dobutamine or Exercise Echocardiography trial, in which patients were randomized to conventional SE (WM analysis only) or real-time MCE (WM and MP analysis). 15 Thus, it seems likely that abnormal MP is more sensitive for detecting at-risk patients who require LR, which would be expected to normalize coronary flow and thus might reduce the incidence of further events. This may in part explain the small number of hard events observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…12 Patients with abnormal MP with and without WM abnormalities were significantly more likely to undergo LR (6.3% [seven of 111] patients with normal MP vs 18.6% [16 of 86] patients with abnormal MP), a finding also noted in the recent Prospective Evaluation of Outcomes with Stress Perfusion Imaging versus Stress Wall Motion Imaging during Dobutamine or Exercise Echocardiography trial, in which patients were randomized to conventional SE (WM analysis only) or real-time MCE (WM and MP analysis). 15 Thus, it seems likely that abnormal MP is more sensitive for detecting at-risk patients who require LR, which would be expected to normalize coronary flow and thus might reduce the incidence of further events. This may in part explain the small number of hard events observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…As far as WM assessment is concerned, cSE‐WMP also has the advantage of maximizing test feasibility over standard stress echocardiography, with quality of acoustic windows not representing an issue when taking advantage of ultrasound contrast media 15. Still, the few studies assessing cSE‐WMP for prognosis do not address its value specifically in predicting true ischemic events (cardiac death and nonfatal acute myocardial infarction [MI]),10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 and it is not known how the use of cSE‐WMP as a gatekeeper to coronary angiography and subsequent revascularization does relate to long‐term outcome in subsequently revascularized and nonrevascularized patients. Previous cSE‐WMP studies reported only on combined end points with prevalence of all‐cause deaths, half of them represented by cancer deaths, pneumonia, or other diseases that may not be directly influenced by coronary ischemia at stress testing 10, 11, 12, 13, 14.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this excellent performance, CCTA has limitations in cases of severe calcified coronary arteries and has substantial motion artefacts. To overcome these problems, stress single-photon emission CT (SPECT),2 stress echocardiography3 and MRI4 have been used simultaneously. Recent studies demonstrated that pharmacological adenosine stress CT myocardial perfusion imaging (MPI) is a promising method for the detection of CAD;5 however, this method requires additional contrast medium and radiation exposure.…”
Section: Introductionmentioning
confidence: 99%